Topical antiseptics for chronic suppurative otitis media - Head, K; Chong, L-Y; Bhutta, MF; Morris, PS; Vijayasekaran, S; Burton, MJ; Schilder, AGM; Brennan-Jones, CG (Cochrane Collaboration, 2020)
Background Chronic suppurative otitis media (CSOM), sometimes referred to as chronic otitis media (COM), is a chronic inflammation and infection of the middle ear and mastoid cavity, characterised by ear discharge (otorrhoea) through a perforated tympanic membrane. The predominant symptoms of CSOM are ear discharge and hearing loss. Topical antiseptics, one of the possible treatments for CSOM, inhibit the micro‐organisms that may be responsible for the infection. Antiseptics can be used alone or in addition to other treatments for CSOM, such as antibiotics or ear cleaning (aural toileting). Antiseptics or their application can cause irritation of the skin of the outer ear, manifesting as discomfort, pain or itching. Some antiseptics (such as alcohol) may have the potential to be toxic to the inner ear (ototoxicity), with a possible increased risk of causing sensorineural hearing loss, dizziness or tinnitus.